Prinsip dasar ekonomi syariah dan relevansinya terhadap ayat-ayat ekonomi dalam Al-Quran - Tasriani, Tasriani; Hanif, Khairul (STAI Auliaurrasyidin Tembilahan, 2025)
Islamic Economics is an economic system based on sharia principles, which are sourced from the Qur'an and hadith. The main objective of Islamic economics is to create prosperity, justice, and socio-economic balance. This study aims to examine the basic principles of Islamic economics and the relevance of economic verses in the Qur'an in forming an economic system that is just and in accordance with Islamic teachings. This study uses a type of library research with data collection techniques using documentation. In the Qur'an, there are several basic principles that are the main foundations in the implementation of Islamic economics, such as the principle of monotheism, the principle of justice, the prohibition of usury, zakat and alms as instruments of Islamic economics, the permissibility of business, and freedom of business as long as it does not violate sharia. Thus, these basic principles of Islamic economics are in accordance with the main values ​​in economic verses that are relevant to current economic practices, namely economic balance, the principle of trade, the prohibition of monopoly and injustice, and the obligation to pay zakat and share.